Economic Diplomacy of the Russian Federation: Prospects for the Development of an Eff ective Export Support System - A. A. Naryshkin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Search for the new markets and niches for national exports is one of the core objectives of economic diplomacy in any modern state. For the Russian Federation this issue acquires particular relevance under present conditions, since the expansion of industrial exports is designed to reduce dependence on commodity exports, strengthen national competitiveness, ensure economic growth, and, correspondingly improve the quality of life of its population. In this regard, eff ective foreign economic activities are essential to the policy, aimed at ensuring the real sovereignty. The paper examines the key elements of non-primary export support system in the Russian Federation. This research is based on both offi cial documents and modern academic literature on this issue and on the author’s personal experience gained while working in a number of relevant state institutions and development agencies, as well as commercial organizations. The first section provides an overview of the key forms and instruments of export support in general, as well as describes the history and the current state of the Russian export support system. The author focuses on the activities of the national trade missions abroad, the Russian Export Center and intergovernmental commissions for trade, economic, scientifi c and technical cooperation. The author notes that many institutions within the framework of the state export support in the Russian Federation are just emerging and face many challenges and diffi culties. The latter include, primarily, the lack of inter-agency co-operation and policy coherence. There are no common operating standards or a unifi ed system of foreign offi ces. On this basis, in the second section the author outlines a number of recommendations to improve the eff ectiveness of the Russian export support system. The author concludes that for the eff ective functioning of this system, it is necessary to harmonize the work and activities of its institutions. The latter should prioritize the needs of particular regions of the Russian Federation, coordinate their eff orts with regional export support centers and business associations. In this regard, the author highlights the potential of the project to create a Unifi ed Export Promotion System, but admits that it has to be started from scratch. In addition, the paper outlines a set of specifi c recommendations that, if carried out consistently, might also contribute to the promotion of Russian goods to foreign markets and ensure the diversifi cation of the country’s economy.